Diencephalic syndrome: A rare and easily overlooked cause of failure to thrive - Dejkhamron P. (2014)
Background: Diencephalic syndrome (DS) is an uncommon cause of failure to thrive in infants and young children. The major manifestations are emaciation, hyperkinesia, and euphoria. Most patients have a tumor in the hypothalamic-optic chiasma region. Case Report: Two children, aged 14 months and 5 years 9 months, who presented with classic features of DS at an onset of 2 and 3 months respectively, were reported. Neurologic examination was normal, except for papilledema in the second child. Imaging of the brain showed a suprasellar mass, identified as pilocytic astrocytoma in both cases. The first case was lost to follow up. The latter underwent partial resection of the tumor and received radiotherapy postoperatively. He gradually gained in weight and height. Conclusion: DS should be a differential diagnosis in any children with emaciation despite adequate caloric intake and an inappropriately euphoric mood. Awareness of this syndrome, careful history taking, general detail as well as neurological examination including fundoscopic examination and appropriated investigations are crucial.